Gender-Dependent Differences in Patients Undergoing Tricuspid Valve Surgery - Pfannmueller, Bettina; Eifert, Sandra; Seeburger, Jörg; Misfeld, Martin; Borger, Michael; Mende, Meinhard; Garbade, Jens; Mohr, Friedrich (The Thoracic and Cardiovascular Surgeon, 2013)
Objectives The proportion of women in tricuspid valve (TV) surgery is almost 60% and above, especially in redo surgery. Is there a different epidemiology for male or female patients regarding the incidence of TV regurgitation? Are there differences in the peri- and postoperative outcome in male and female patients? In these questions, we were interested in and investigated our database of patients with isolated TV surgery.Methods We present a retrospective analysis of 92 patients (37 men and 55 women) undergoing isolated TV surgery due to symptomatic severe tricuspid regurgitation and/or due to active endocarditis between May 1997 and August 2010. Mean age was 60.5 ± 15.8 years, mean log European System for Cardiac Operative Risk Evaluation (EuroSCORE) was 12.1 ± 11.3%, 51.4% of the operations were redos (men: 27%, women: 65%, p < 0.001), 36% due to active endocarditis (men: 62%, women: 18%, p < 0.001). Follow-up was 95% complete with a mean duration of 34.2 ± 33.0 months.Results Overall 30-day mortality was 5.4% (men: 5.4% and women: 5.5%). Five-year survival was 70.2 ± 11.4 versus 76.3 ± 6.8% (p = 0.3); 5-year freedom from TV-related reoperation was 95.8 ± 4.1 versus 84.6 ± 8.5% for men and women (p = 0.4). There was no significant gender-dependent difference regarding the global postoperative outcome. In a binary logistic regression analysis with the dependent variable gender, the categories age, log EuroSCORE, endocarditis, previous cardiac surgery, and preoperative cardiac rhythm, an odds ratio of 0.17 for men regarding the factor endocarditis (95% confidence interval [CI]: 0.05 to 0.57; p = 0.004) was shown, as well as an odds ratio of 3.2 for women regarding the factor previous cardiac surgery (95% CI: 1.0 to 10.1; p = 0.04) and an odds ratio of 5.9 regarding the factor presence of a permanent pacemaker (95% CI: 1.4 to 24.7; p = 0.02).Conclusions We were not able to find significant gender-dependent differences in the postoperative outcome after isolated TV surgery, but there seem to be demographic gender-dependent differences regarding the reasons for TV surgery, which could influence the treatment of patients.
Keywords: tricuspid valve; heart valve surgery; cardiac